2017
DOI: 10.1111/jdv.14583
|View full text |Cite
|
Sign up to set email alerts
|

Biologics combined with conventional systemic agents or phototherapy for the treatment of psoriasis: real‐life data from PSONET registries

Abstract: Methotrexate was the most commonly used concomitant treatment for patients on a biologic. Wide geographical variations in treatment selection and persistence of combination treatment exist. Data derived from ongoing studies may help to determine whether combined treatment is superior to biologic monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 39 publications
2
31
1
3
Order By: Relevance
“…Confounding by indication was possible; disease severity was generally mild in all cohorts and was within the same range across existing and initiated therapy, but some differences were seen for prior csDMARD use. Previous registry studies provided similar results but were conducted either outside the United States [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] or they used a subset of PsA patients from a registry in the United States that was designed primarily for patients with rheumatoid arthritis [40][41][42][43]. Our study used data from a registry in the United States that was specifically designed to collect information about patients with PsA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Confounding by indication was possible; disease severity was generally mild in all cohorts and was within the same range across existing and initiated therapy, but some differences were seen for prior csDMARD use. Previous registry studies provided similar results but were conducted either outside the United States [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] or they used a subset of PsA patients from a registry in the United States that was designed primarily for patients with rheumatoid arthritis [40][41][42][43]. Our study used data from a registry in the United States that was specifically designed to collect information about patients with PsA.…”
Section: Discussionmentioning
confidence: 95%
“…Patient and physician global disease assessments are combined with 28 swollen and tender joint counts to calculate the Clinical Disease Activity Index (CDAI) from 0 to 76, where < 2.9 is remission, 2.9-10.0 low disease activity, 10.1-22.0 moderate disease activity, and > 22.0 high disease activity [14]. Disease Activity in Psoriatic Arthritis (DAPSA) scores are calculated from joint counts (68 tender/66 swollen), CRP, and patient assessments of disease activity and pain, yielding scores consistent with remission (0-4) or mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), or high (> 28) disease activity [15]. Patients use the Work Productivity and Activity Impairment questionnaire to report the effect of PsA/SpA on work (percentage of hours missed, impairment while at work, and work hours affected) and daily activities [16][17][18].…”
Section: Data Collectionmentioning
confidence: 99%
“…This result is slightly different from what is reported in previous studies. Busard et al 6 investigated the conventional systemic agents or phototherapy combined with biologics and found that methotrexate was most frequently used compound. However, this study only ana-lyzed the concomitant combined treatment during the use of biologics, whereas we investigated the combined treatment with etanercept and the rotational treatment between intermittent etanercept treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, various topical therapies can be used to treat the patients with mild disease of psoriasis, such as topical retinoids, corticosteroids, vitamin D and its analogues . And the combination treatment of topical agents and other adjuvant therapies was the major therapeutic strategy for the severe psoriasis patients; however, its effects are very limited …”
Section: Discussionmentioning
confidence: 99%